Follow-up study of pulmonary function among COVID-19 survivors 1 year after recovery. Issue 3 (September 2021) - Yan, Xiquan; Huang, Huxiang; Wang, Changfeng; Jin, Zhaoxia; Zhang, Zhongwei; He, Jiangming; Yin, Siqing; Fan, Maiying; Huang, Juanshu; Chen, Fang; Zeng, Yong; Han, Xiaotong; et al.
Highlights: Pulmonary function was assessed in individuals who had recovered after a year from COVID-19. Forty-seven (39%) survivors had impaired diffusing capacity during the 1-year follow-up. Fifty (42%) survivors had abnormal total vital capacity during the 1-year follow-up.